Using smart transportation assets to hedge fossil energy markets: Evidence from quantile-based VAR approach - Md. Bokhtiar Hasan; Md. Naiem Hossain; Hosneara Khatun; Gazi Salah Uddin; Mehmet Huseyin Bilgin; Shu Tian (PLoS ONE, 2025)
This study explores the time-varying correlations and quantile spillover connectedness to identify the hedging potential of smart transportation assets for energy markets. The study finds that amid crises like COVID-19 and the Russia-Ukraine conflict, smart transportation indices demonstrate strong safe-haven characteristics against volatility in equity commodity energy and electricity transmission and distribution infrastructure indices. Additionally, the smart transportation, electric vehicle, and drone indices offer limited hedging benefits and safe-haven attributes for carbon emission allowance and natural gas. Furthermore, smart transportation assets are the major spillover transmitters to fossil energy assets across all quantiles. These outcomes hold substantial implications for environmental advocates, investors, and policymakers.